Selection and Validation of Appropriate Reference Genes for Quantitative Real-Time PCR Normalization in Staminate and Perfect Flowers of Andromonoecious Taihangia rupestris - Li, Weiguo; Zhang, Lihui; Zhang, Yandi; Wang, Guodong; Song, Dangyu; Zhang, Yanwen (Frontiers in Plant Science, 2017)
Quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR) is the most commonly used and powerful method for gene expression analysis due to its high sensitivity, specificity, and high throughput, and the accuracy of this approach depends on the stability of reference genes used for normalization. Taihangia rupestris Yu & Li (Rosaceae), an andromonoecious plant, produces both bisexual flowers and unisexual male flowers within the same individual. Using qRT-PCR technique, investigation of the gene expression profiling in staminate and perfect flowers would improve our understanding of the molecular mechanism in regulation of flower formation and sex differentiation in andromonoecious T. rupestris. To accurate normalize the gene expression level in Taihangia flower, 16 candidate reference genes, including 10 traditional housekeeping genes and 6 newly stable genes, were selected based on transcriptome sequence data and previous studies. The expressions of these genes were assessed by qRT-PCR analysis in 51 floral samples, including floral tissues in mature flowers, staminate and perfect flowers across developmental stages. By using geNorm, NormFinder, BestKeeper, and comprehensive RefFinder algorithms, ADF3 combined with UFD1 were identified as the optimal reference genes for staminate flowers, while the combination of HIS3/ADF3 was the most accurate reference genes for perfect and all floral samples, respectively. For floral tissues, HIS3/UFD1was the most suitable reference genes. Furthermore, two target genes, TruPI and TruFBP24, involved in floral organ identity were selected to validate the most and least stable reference genes in floral tissues, staminate and perfect flowers at different developmental stages, indicating that the use of inappropriate reference genes for normalization will lead to the adverse results. The reference genes identified in this study will improve the accuracy of qRT-PCR quantification of target gene expression in andromonoecious T. rupestris flowers, and will facilitate the functional genomics studies on flower development and sex differentiation in the future.